2018
DOI: 10.1504/aajfa.2018.10009896
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of diversification benefits of commodity futures using Markov regime-switching approach

Abstract: This study investigates the hedge and safe haven properties of individual commodity futures against stock market movements using a nonlinear regime-switching framework. Based on the results of Brock, Dechert and Scheinkman (BDS) test and information selection criterion, Markov-switching vector auto-regression (MS-VAR) model is applied with three regimes for gold and silver futures and with two regimes for crude oil, copper and zinc futures. The results demonstrate strong hedge and weak safe haven property of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Many of these investors are using commodity futures as an investment vehicle for making strategic and tactical allocations. Strategic allocations of commodity futures are highly valued due to the benefits of the long-term equity-like returns, the diversification benefits, and the inflation hedging potentials (Bodie & Rosansky, 1980;Jensen, Johnson & Mercer, 2002;Erb & Harvey, 2006;Gorton & Rouwenhorst, 2006;Jaiswal & Uchil, 2016;2018a;2018b). In addition to the strategic asset allocations, commodity futures are used for tactical asset allocations to generate abnormal alphas as shown by previous studies (Erb & Harvey, 2006;Miffre & Rallis, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these investors are using commodity futures as an investment vehicle for making strategic and tactical allocations. Strategic allocations of commodity futures are highly valued due to the benefits of the long-term equity-like returns, the diversification benefits, and the inflation hedging potentials (Bodie & Rosansky, 1980;Jensen, Johnson & Mercer, 2002;Erb & Harvey, 2006;Gorton & Rouwenhorst, 2006;Jaiswal & Uchil, 2016;2018a;2018b). In addition to the strategic asset allocations, commodity futures are used for tactical asset allocations to generate abnormal alphas as shown by previous studies (Erb & Harvey, 2006;Miffre & Rallis, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Normally, it is observed that the prices of an asset which move with inflation can be used as a hedge against stock and bond market plunge. As stock and bond markets fail to sustain their value during the period of unexpected inflation (Jaiswal and Uchil, 2015). These facts are providing the strong motivation to do an empirical analysis of hedge and safe haven property of gold futures against stock and bond market movements.…”
Section: Introductionmentioning
confidence: 99%